Impaired metabolism of oligodendrocyte progenitor cells and axons in demyelinated lesion and in the aged CNS. (June 2022) - Zhao, Jing-Wei; Wang, Di-Xian; Ma, Xiao-Ru; Dong, Zhao-Jun; Wu, Jian-Bin; Wang, Fan; Wu, Yang
Abstract: The key pathology of multiple sclerosis (MS) comprises demyelination, axonal damage, and neuronal loss, and when MS develops into the progressive phase it is essentially untreatable. Identifying new targets in both axons and oligodendrocyte progenitor cells (OPCs) and rejuvenating the aged OPCs holds promise for this unmet medical need. We summarize here the recent evidence showing that mitochondria in both axons and OPCs are impaired, and lipid metabolism of OPCs within demyelinated lesion and in the aged CNS is disturbed. Given that emerging evidence shows that rewiring cellular metabolism regulates stem cell aging, to protect axons from degeneration and promote differentiation of OPCs, we propose that restoring the impaired metabolism of both OPCs and axons in the aged CNS in a synergistic way could be a promising strategy to enhance remyelination in the aged CNS, leading to novel drug-based approaches to treat the progressive phase of MS.